Pengembangan Aplikasi Augmented Reality Pada Mata Pelajaran Bahasa Inggris Untuk Kelas 1 Sekolah Dasar - Fendy Nanang Setiawan; Mohammad Zaenal Abidin; Dwi Ratnawati (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2023)
This research was developed to overcome problems in students who tend to get bored in English subjects with book media. This research aims to develop AugmentedÂ Reality in English subject for grade 1 elementary school. The research method used in this study namely research and development (R&D) with the ADDIE application development model (Analysis, design, development, implementation, and evaluation), in this study is limited to stage implementation. Products are developed using game engine Unity 3D and Vuforia. Data analysis techniques in this study will use descriptive and quantitative analysis techniques. The data collection instrument used was a questionnaire with 8 respondents. The end result of the product is an educational game-based application Augmented Reality learning English which contains 3D objects, descriptions, sentences and sounds from objects that are run. The results of the feasibility test obtained an average score of 81.90% in the very good category. With the application Augmented Reality this is expected to help 1st grade elementary school students in learning English.